2018
DOI: 10.3390/molecules23092376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cultivar Differences of Blueberry Wines Using GC-QTOF-MS and Metabolic Profiling Methods

Abstract: A non-targeted volatile metabolomic approach based on the gas chromatography-quadrupole time of fight-mass spectrometry (GC-QTOF-MS) coupled with two different sample extraction techniques (solid phase extraction and solid phase microextraction) was developed. Combined mass spectra of blueberry wine samples, which originated from two different cultivars, were subjected to orthogonal partial least squares-discriminant analysis (OPLS-DA). Principal component analysis (PCA) reveals an excellent separation and OPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Interestingly, we found that ‘O’Neal’ blueberry contained two sesquiterpenes E‐asarone and Z‐asarone, which are firstly reported in blueberries. Our results were consistent with the previous finding that E‐ and Z‐asarone were detected in O’Neal blueberry wines 13,14 . Although E‐ and Z‐asarone are often reported in plants, especially in essential oils, 31 due to the low volatility, they may not contribute to the overall aroma of the blueberries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found that ‘O’Neal’ blueberry contained two sesquiterpenes E‐asarone and Z‐asarone, which are firstly reported in blueberries. Our results were consistent with the previous finding that E‐ and Z‐asarone were detected in O’Neal blueberry wines 13,14 . Although E‐ and Z‐asarone are often reported in plants, especially in essential oils, 31 due to the low volatility, they may not contribute to the overall aroma of the blueberries.…”
Section: Resultssupporting
confidence: 92%
“…Farneti et al analysed the volatile composition of eleven different blueberry cultivars and found that for the most cultivar, aldehydes, alcohols, terpenoids and esters can be used as putative biomarkers to evaluate the blueberry aroma variations 4 . Other reports also showed that terpenes such as linalool and α‐terpineol were important varietal compounds in blueberries which could affect the aroma of the corresponding products such as blueberry wines 13,14 . Although some research papers have been published on sensory characteristics of blueberries, 15,16 very little information is available regarding the relationship between sensory attributes and their volatile composition.…”
Section: Introductionmentioning
confidence: 99%
“…Farneti et al [ 16 ] analyzed the volatile composition of eleven different blueberry cultivars and found that for most cultivars, aldehydes, alcohols, terpenoids, and esters can be used as putative biomarkers to evaluate the blueberry aroma variations. Recent reports on blueberry wine and vinegar also showed that terpenes such as linalool and α-terpineol were important berry-derived aroma compounds in blueberries [ 17 , 18 ]. Zhu et al [ 19 ] reported that esters, aldehydes, C13-norisoprenoids, as well as several terpenes and eugenol, were the aroma-active compounds in freshly pressed blueberry juice.…”
Section: Introductionmentioning
confidence: 99%
“…e objective of this work was to study the quality variations among some major blueberry cultivars by a fusion analysis of some physical and chemical factors, nutritional ingredients, and antioxidant abilities. In order to reveal the key factors among different blueberry cultivar, besides the unsupervised principal component analysis (PCA), the supervised partial least squares discriminant analysis (PLSDA) was also used to develop multiclass classification models using feature sets selected by the global particle swarm optimization (PSO) algorithm [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%